Effects of Grain Orientation on Stress State near Grain Boundary of Austenitic Stainless Steel Bicrystals - Fu-qiang Yang; He Xue; Ling-yan Zhao; Xiu-Rong Fang (Advances in Materials Science and Engineering, 2018)
The stress state at the crack tip of structural components in nuclear power plants used in the SCC quantitative prediction models is based on the assumption that the polycrystalline material is isotropic and homogeneous at present. However, the crystals in polycrystalline materials are anisotropic with different orientations, which would induce a nonuniform stress to cause the initiation and propagation of SCC. By using a finite element method, the elastic responses of anisotropic behaviors of austenitic stainless steel bicrystals are studied. The results indicate that the stress distribution near GBs depends strongly on the crystal orientation. A larger Mises stress concentration exists on the GB with larger stiffness along the load direction. The Mises stress difference is higher in the bicrystal with bigger elastic modulus difference of two neighboring grains along the tensile axis. In the bicrystal with GB perpendicular to the tensile axis, the grain orientation has little effects on the Mises stress far from the GB in both grains. The strain inconsistency in bicrystals is affected by the mismatch of two neighboring grains. The larger the elastic modulus differences between two neighboring grains caused by misorientation, the larger the strain inconsistency in the bicrystal.